Inhibition of Plasmodium Hepatic Infection by Antiretroviral Compounds - Machado, Marta; Sanches-Vaz, Margarida; Cruz, João P.; Mendes, António M.; Prudêncio, Miguel (Frontiers in Cellular and Infection Microbiology, 2017)
Recent WHO guidelines on control of human immunodeficiency virus (HIV) call for the widespread use of antiretroviral (AR) therapy (ART) for people living with HIV. Given the considerable overlap between infections by HIV and Plasmodium, the causative agent of malaria, it is important to understand the impact of AR compounds and ART regimens on infections by malaria parasites. We undertook a systematic approach to identify AR drugs and ART drug combinations with inhibitory activity against the obligatory hepatic stage of Plasmodium infection. Our in vitro screen of a wide array of AR drugs identified the non-nucleoside reverse transcriptase inhibitors efavirenz and etravirine (ETV), and the protease inhibitor nelfinavir, as compounds that significantly impair the development of the rodent malaria parasite P. berghei in an hepatoma cell line. Furthermore, we show that WHO-recommended ART drug combinations currently employed in the field strongly inhibit Plasmodium liver infection in mice, an effect that may be significantly enhanced by the inclusion of ETV in the treatment. Our observations are the first report of ETV as an anti-Plasmodial drug, paving the way for further evaluation and potential the use of ETV-containing ARTs in regions of geographical overlap between HIV and Plasmodium infections.